Improved line list of 12CH4 in the 4100–4300 cm−1 region - Rodina, Alena A.; Nikitin, Andrei V.; Manceron, Laurent; Thomas, Xavier; Daumont, Ludovic; Rey, Michaël; Sung, Keeyoon; Protasevich, Alexander E.; Tashkun, Sergey A.; Tyuterev, Vladimir G. (Journal of Quantitative Spectroscopy and Radiative Transfer)
Four spectra of methane in natural isotopic abundance in the 4100-4300 cm(-1) region were recorded by using a Fourier transform spectrometer in Reims, France at long paths (202 m, 602 m, 1604 m and 1804 m) and different pressures. Additional spectra of (CH4)-C-12 covering the same region were obtained at 100-123 K for different pressures, 93 m path length at Synchrotron SOLEIL in Paris for different pressures and were used to measure low-J lines. Spectra of (CH4)-C-12 and (CH4)-C-13 obtained at 80 K at JPL in Pasadena were used for additional frequency calibrations. Line positions and intensities were retrieved by non-linear least-squares curve-fitting procedures and analyzed using effective Hamiltonian and effective dipole transition moment models. A new measured line list contains positions and intensities for 12,378 features. Quantum assignments were made for more than 11,520 new transitions, which represent similar to 99% of the integrated line intensity observed in this region. Some of 4556 hot band transitions for (Dyad - Tetradecad) system were assigned. The resulting list of lines is significantly more accurate than previous empirical compilations. All assigned 6963 line positions were fitted to RMS standard deviations of 0.0015 cm(-1). The sum of the observed intensities between 4100 and 4300 cm(-1) falls within 5% of the predicted value from ab initio variational calculations reported in the TheoReTS database (http: //theorets.univ-reims.fr ; http://theorets.tsu.u). (C) 2021 Elsevier Ltd. All rights reserved.